1996
DOI: 10.1111/j.1349-7006.1996.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of the Cell Cycle with Colchicine Enhances the Growth Advantage of Diethylnitrosamine‐initiated Hepatocytes in Rats

Abstract: The effect of cell cycle disturbance due to colchicine on the induction of enzyme‐altered foci during liver regeneration in rats was studied. For initiation, diethylnitrosamine (DEN) at a dose of 10 mg/ kg was injected intraperitoneally and partial hepatectomy (PH) was performed 4 h thereafter. Colchicine at doses of 0, 0.1, 0.25 and 0.5 mg/kg was injected intraperitoneally 1 and 3 days after the initiation, followed by application of selection pressure consisting of 2‐acetylaminofluorene (AAF) and carbon tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…With the exogenous agent, the method for the production of HCCs was as previously described. 3,4) Animals received DEN intraperitoneally at a dose of 10 mg/ kg body weight followed after 4 h by PH performed by the method of Higgins and Anderson. 40) Colchicine at a dose of 0.5 mg/kg body weight was injected intraperitoneally 1 and 3 days after DEN treatment.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exogenous agent, the method for the production of HCCs was as previously described. 3,4) Animals received DEN intraperitoneally at a dose of 10 mg/ kg body weight followed after 4 h by PH performed by the method of Higgins and Anderson. 40) Colchicine at a dose of 0.5 mg/kg body weight was injected intraperitoneally 1 and 3 days after DEN treatment.…”
Section: Animalsmentioning
confidence: 99%
“…We have reported that a cell cycle disturbance induced in DEN-initiated hepatocytes by colchicine gives a growth advantage to formation of putative preneoplastic lesions under conditions of partial hepatectomy (PH) and selection pressure, so that a high incidence of HCCs can be obtained within a short period. 3,4) Since our studies revealed differential effects of chemopreventive agents in our two liver models, 5,6) the possibility arises of different mechanisms underlying endogenous and exogenous hepatocarcinogenesis in rats.…”
mentioning
confidence: 91%
“…With the exogenous agent, the method for the production of HCCs was as previously described [1,2]. Fifteen animals received DEN at a single intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…N ‐nitrosodiethylamine (DEN) is one of the best‐known liver carcinogens in rats. We have reported that a cell‐cycle disturbance induced in DEN‐initiated hepatocytes by colchicine gives a growth advantage to putative preneoplastic lesions under conditions of partial hepatectomy and selection pressure, so that a high incidence of hepatocellular carcinomas (HCCs) can be obtained within a short latent period [1,2]. We have also demonstrated high yields of HCCs associated with cirrhosis caused by chronic administration of a CDAA diet that does not contain any known carcinogens [3].…”
Section: Introductionmentioning
confidence: 99%
“…N ‐nitrosodiethylamine (DEN) is one of the best‐known liver carcinogens in rats. We have reported that a cell‐cycle disturbance induced in DEN‐initiated hepatocytes by colchicine gives a growth advantage to putative preneoplastic lesions under conditions of partial hepatectomy and selection pressure, so that a high incidence of hepatocellular carcinomas (HCCs) can be obtained within a short latent period [255,266]. We also have shown high yields of HCCs associated with cirrhosis that are caused by long‐term administration of a choline‐deficient L ‐amino acid–defined (CDAA) diet, which does not contain any known carcinogens [27].…”
Section: Introductionmentioning
confidence: 99%